Pendampingan Model Pembelajaran Kooperatif Bagi Guru Matematika SMP/MTs se-Kabupaten Maros - Nirfayanti, Nirfayanti; Ernawati, Ernawati; Khaerani, Khaerani; Nasir, A. Muhajir; Rahmawati, Rahmawati; Syamsuriyawati, Syamsuriyawati; Setyawan, Dedy (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Teacher quality can be improved by increasing knowledge about various methods, approaches and strategies that can be applied in learning to overcome learning problems in the classroom so that innovative learning can be realized which will maximize student achievement. In connection with this problem, the cooperative learning model was socialized to improve students' mathematical generalization abilities. This community service aims to socialize the application of the Active, Collaborative and Inductive (AKI) Cooperative learning model to teachers in Maros Regency. This activity was attended by 23 teachers and lecturers from various schools and universities. During the activity, the teachers were interested and motivated to develop creative mathematics teaching skills using the AKI type cooperative learning model as a solution to the low mathematical generalization abilities experienced by students.